Effects of psychological and institutional factors on entrepreneurial intention among undergraduate students in Nigeria - Bularafa, Bukar Ali (2018)
Today, university education in Nigeria is no longer a guarantee for university graduates automatic employment sequel to the tight labour market condition. However, the graduates are still reluctant to choose entrepreneurship as a feasible occupation, even with the high job scarcity. Because, the level of entrepreneurial awareness among university graduates in Nigeria is palpably low. This can be justified considering the high rate of unemployment among these graduates. Thus, there is need for an empirical study to determine factors that have an effect on the student’s entrepreneurial potentials in Nigeria. The main objective of the study, therefore, is to examine the effect of psychological factors (self-efficacy, risk-taking propensity, locus of control, innovation, and need for achievement) and institutional factors (university entrepreneurship education, and government support programmes) on entrepreneurial intention among undergraduate students of University of Maiduguri, Abubakar Tafawa Balewa University, Bauchi and Modibbo Adama University of Technology, Yola, North-eastern, Nigeria. Earlier research investigated the effects of psychological factors, institutional factors and culture in isolation from each other and so found inconsistent and inconclusive results. Hence, the objective of the current study is twofold: first to examine the direct effect of psychological and institutional factors on entrepreneurial intention. Second, it seeks to determine whether culture influences the relationship between entrepreneurial intention and its psychological and institutional determinants. The study employs survey research design. The population for the study was 3,024 final year undergraduate students of the three selected universities in North-eastern, Nigeria. Data were collected from a sample of 383 students through a questionnaire. Descriptive statistics and SEM, using AMOS graphics were employed to analyse the data. Interestingly, the findings contradict the research claims indicating that majority of the respondents showed a high level of entrepreneurial intention, though differences were noticed among students of the three universities regarding the level of their entrepreneurial intention. Students from the University of Maiduguri indicate low entrepreneurial intention, while students from Abubakar Tafawa Balewa University, Bauchi and the Modibbo Adama University of Technology, Yola indicate a high level of entrepreneurial intention. The findings further revealed that there is a positive effect between all the variables; self-efficacy, risk-taking propensity, the locus of control, innovation, need for achievement, university entrepreneurship education, government support programmes and entrepreneurial intention among the students. In addition, the results indicate the greater effect are from government support programmes and innovation. However, the moderation test revealed that culture moderates the effect of all the variables on entrepreneurial intention among university undergraduate students. Therefore, based on the findings of the study that indicate students have high level of entrepreneurial intention, it recommends that government and policymakers should develop a policy framework that would make graduates actualise their intention of starting a business through the provision of support and assistance. Also university curriculum should focus on independence and innovation. Furthermore, future research should be conducted to examine the factors inhibiting entrepreneurship among these graduates.